Design of A Braille Printer Based on ESP32 Microcontroller with Voice Input - Beatrix, Maria; Wahab, Wahidin; Wulandari, Meirista (Tecno Scientifica Publishing, 2025)
Braille is a tactile phonetic alphabet system invented by Louis Braille, a blind teacher from France, in the 1800s. The Braille system was recognized as